2003
DOI: 10.1351/pac200375050577
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic control of electron-transfer processes

Abstract: Catalytic control of electron-transfer processes is described for a number of photoinduced and thermal electron-transfer reactions, including back electron transfer in the charge-separated state of artificial photosynthetic compounds. The intermolecular and intramolecular electron-transfer processes are accelerated by complexation of radical anions, produced in the electron transfer, with metal ions that act as Lewis acids. Quantitative measures to determine the Lewis acidity of a variety of metal ions are giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Redox-inactive metal ions can both act as a Lewis acid and play a pivotal role in promoting various reactions [ 44 ]. Previous studies have shown that the binding of ionic metal species with radical anions plays an important role in mediating the electron-transfer reactivity of the substrate [ 45 ]. The complexation of to metal ions can be achieved by photo-induced electron transfer from the excited state of a dimeric organic compound, in which the catalytic process acts as a unique two-electron donor and then yields two monomeric cations along with two –metal ion complex radical ions [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Redox-inactive metal ions can both act as a Lewis acid and play a pivotal role in promoting various reactions [ 44 ]. Previous studies have shown that the binding of ionic metal species with radical anions plays an important role in mediating the electron-transfer reactivity of the substrate [ 45 ]. The complexation of to metal ions can be achieved by photo-induced electron transfer from the excited state of a dimeric organic compound, in which the catalytic process acts as a unique two-electron donor and then yields two monomeric cations along with two –metal ion complex radical ions [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review focuses on acid catalysis of both Brønsted acids and metal ions acting as Lewis acids by binding these acids to A to accelerate ET reactions from D to A. [32][33][34][35][36][37][38][39][40][41][42] The fundamental concept of acid catalysis in ET chemistry is shown in Scheme In the presence of a Lewis acid (LA: H + or metal ions), a LA binds to a base (A •-) to produce A •--LA. Because of the strong binding in A •--LA, ET from D to A becomes exergonic to produce D •+ and A •--LA, [32][33][34][35][36][37][38][39][40][41][42] followed by C C bond formation to produce D-A after releasing LA.…”
Section: Introductionmentioning
confidence: 99%
“…They are readily synthesized, and their properties are easily tuned by substitution and metalation. In addition, the aggregated state guarantees increased absorption cross-sections and an efficient use of the solar spectrum for energy conversion [24][25][26]. Based on the above concept, numerous reports have appeared discussing photoinduced charge separation and light energy conversion in porphyrin-CNT and porphyrin-fullerene assemblies, so far [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%